Tingkat Pengungkapan Corporate Social Responsibility Bank Syariah di Indonesia - Amalia Imroatul Azizah; Muhammad Nur A. Birton (Jurnal Akuntansi dan Keuangan Islam, 2015)
The implementation of corporate social responsibility has entered a new era is noexception in Islamic companies, especially of Islamic banking. Islamic Social ReportingIndex is one way of measuring and reporting social responsibility for sharia entity. Thisstudy aimed to describe the practice of social responsibility disclosure based IslamicSocial Reporting Index on Islamic banks in Indonesia is associated with the size of theCommercial Bank Based on Business Activities (BUKU). Using comparative descriptive method by means of content analysis on the elements of financial statements, thisstudy using Islamic banks data annual report published in 2011-2013. The results showedan increase in items disclosure in each group BUKU. In general, Islamic banks ISRBUKU 2 disclosure scores higher than group Islamic banks BUKU 1. That is, the Islamicbanks with equity of more than Rp 1 trillion to less than Rp 5 trillion disclose socialresponsibility in a more specific and detailed than the equity less from Rp 1 trillion.